Elands Bay Cave: keeping an eye on the past - Parkington, J. E. (Southern African Humanities, 2016)
Elands Bay Cave has been episodically occupied for many tens of thousands of years, but apparently always in fairly brief visits. It therefore contains an intermittent but sequentially organized record of environmental and behavioural events over a time period of perhaps 150 000 years. Here I look at the later Holocene record and assess what it reveals about marine food exploitation by hunter gatherers and later pastoralist groups. Because we have similar records from several other small caves, rock shelters and open sites around the Verloren Vlei and the associated shoreline, we can recognise periods of common use and disuse and understand the intermittent and changing use of the local shoreline resources over the past 5000 years.